Abnormal patterns of D-type cyclin expression and G1 regulation in human head and neck cancer - Bártková, Jiřina; Lukáš, Jiří; Müller, Heiko; Strauss, Michael; Gusterson, Barry; Bártek, Jiří (Cancer research, 1995)
D-type cyclins are proto-oncogenic cell cycle regulators implicated in the pathogenesis of several types of cancer. Amplification of the cyclin D1 gene has been described in 30-50% of human head and neck squamous cell carcinoma (HNSCC). Using immunohistochemistry on archival specimens of human HNSCC and a mAb DCS-6, which is specific for cyclin D1, strong positivity was found in nuclei of 9 (17%) of 52, a moderately elevated signal in 16 (31%) of 52, and weak staining comparable with normal tissues in 27 (52%) of 52 patients. Immunoblotting analysis of five HNSCC-derived cell lines showed three distinct spectra of D-type cyclin proteins: cyclin D1 only (in UMSCC-2 and UMSCC-22b cell lines with 11q13 amplification), cyclins D1 and D3 (in HN5 and HN6), or cyclins D1, D2, and D3 (in UMSCC-1). Electroporation of neutralizing antibodies demonstrated requirement for cyclin D1 in cell cycle progression of all five HNSCC cell lines. Cyclin D2 was essential and showed a cooperative effect with cyclin D1 in positive regulation of G1 in UMSCC-1 cells. These data are consistent with the proposed oncogenic role of cyclin D1 in HNSCC and open up the way for immunohistochemical assessment of cyclin D1 aberrations in archival clinical specimens. It is also suggested that excessive levels of cyclin D1 alone or cooperative effects of several D-type cyclin proteins may lead to deregulation of G1 control in distinct subsets of human HNSCC. These results are discussed in the context of possible functional redundancy of D-type cyclins and the role of the D-type cyclin/p16-CDKN2/pRB pathway in tumorigenesis.
Keywords: zalévání tkání do parafínu; G1 Phase; Paraffin Embedding; onkogenní proteiny; Cyclins; imunohistochemie; lidé; Cyclin D2; Immunohistochemistry; nádory hlavy a krku; Cyclin D1; cyklin D2; Head and Neck Neoplasms; Humans; G1 fáze; Oncogene Proteins; cyklin D1; cykliny; spinocelulární karcinom; Carcinoma, Squamous Cell